Spontaneous Order - Always Efficient? Comment on Patrick Simon's: "Emergence of a European Ius Commune" - Roland Kirstein (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1997)
Ius Commune describes the spontaneous development of a european contract law by adaptive behavior of contracting parties to competing law systems and their interpretations by jursidiction. The idea of spontaneous law harmonization is appealing, since its result is independent of centraized planning. However, spontaneous order might be inefficient, due to adaption costs and inefficient equilibria, as the paper demonstrates, making use of simple examples. – – Ius Commune beschreibt die spontane Entwicklung eines europäischen Vertragsrechts durch Anpassungsverhalten potentieller Vertragsparteien an konkurrierende Normensysteme und ihre Interpretationen durch Richter. Diese spontane Art der Rechtsharmonisierung hat den Vorteil, daß Ihre Ergebnis nicht von zentralistsicher Planung abhängt. Der Beitrag zeigt an einfachen Beispielen auf, daß spontane Ordnung jedoch Anpassungskosten aufwirft und zu ineffizienten Gleichgewichten führen kann.
Keywords: K12; D71; C72; 330; spontaneous order; coordination failure; law harmonization; optimum legal areas